Microbial Community Modeling: Prediction of Microbial Interactions and Community Dynamics - Hyun-Seob Song (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
Investigating the microbiome is on the frontier of science. It has the potential to resolve many issues in the realms of energy, food, human health, the environment, and biotechnology. Scientists are trying to understand, in a fundamental way, how microbes influence each other and how they organize into interaction networks. These are the keys to predicting and engineering community function and properties of the microbiome. In this regard, mathematical modeling and computational analysis play an increasing role. This book is a collection of contributions from lead scientists in the field. It provides innovative approaches and fresh perspectives for modeling environmental communities and engineered microbial consortia. Reading this book will give researchers a solid look at cutting-edge science in microbial community modeling, and at the remaining challenges such modeling poses.